Myocardium at risk by magnetic resonance imaging: head-to-head comparison of T2-weighted imaging and contrast-enhanced steady-state free precession - Ubachs, Joey F.A. (Oxford University Press, 2012)
AIMS: To determine the myocardial salvage index, the extent of infarction needs to be related to the myocardium at risk (MaR). Thus, the ability to assess both infarct size and MaR is of central clinical and scientific importance. The aim of the present study was to explore the relationship between T2-weighted cardiac magnetic resonance (CMR) and contrast-enhanced steady-state free precession (CE-SSFP) CMR for the determination of MaR in patients with acute myocardial infarction. METHODS AND RESULTS: Twenty-one prospectively included patients with first-time ST-elevation myocardial infarction underwent CMR 1 week after primary percutaneous coronary intervention. For the assessment of MaR, T2-weighted images were acquired before and CE-SSFP images were acquired after the injection of a gadolinium-based contrast agent. For the assessment of infarct size, late gadolinium enhancement images were acquired. The MaR by T2-weighted imaging and CE-SSFP was 29 ± 11 and 32 ± 12% of the left ventricle, respectively. Thus, the MaR with T2-weighted imaging was slightly smaller than that by CE-SSFP (−3.0 ± 4.0%; P < 0.01). There was a significant correlation between the two MaR measures (r(2)= 0.89, P < 0.01), independent of the time after contrast agent administration at which the CE-SSFP was commenced (2–8 min). CONCLUSION: There is a good agreement between the MaR assessed by T2-weighted imaging and that assessed by CE-SSFP in patients with reperfused acute myocardial infarction 1 week after the acute event. Thus, both methods can be used to determine MaR and myocardial salvage at this point in time.